2017
DOI: 10.1186/s12952-017-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Work-focused cognitive behavioral intervention for psychological complaints in patients on sick leave due to work-related stress: Results from a randomized controlled trial

Abstract: BackgroundWork-related stress is a global problem with negative implications for individuals and society. The purpose of the current study was to evaluate a stress management intervention for patients on sick leave due to work-related stress complaints using a three-armed randomized controlled design.MethodsParticipants were patients referred from three municipalities to the regional Department of Occupational Medicine. Inclusion criteria were: 1) sick leave due to work-related stress complaints, 2) a diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Christensen et al [31] compared three different intervention programs; Bergström et al [27] compared three different intervention programs with a control group; Dalgaard et al [29] compared an intervention group with two control groups; and Nieuwenhuijsen et al [22] used both a control group and a placebo group. Two different occupational rehabilitation programs were compared in the study by Friedrich et al [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Christensen et al [31] compared three different intervention programs; Bergström et al [27] compared three different intervention programs with a control group; Dalgaard et al [29] compared an intervention group with two control groups; and Nieuwenhuijsen et al [22] used both a control group and a placebo group. Two different occupational rehabilitation programs were compared in the study by Friedrich et al [20].…”
Section: Resultsmentioning
confidence: 99%
“…de Buck et al [19] examined work loss (total incapacity or unemployment) and Detaille et al [1] examined self-efficacy at work and attitudes toward self-management at work as their primary outcomes. There were no secondary findings in six studies [21,26,27,29,31,33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalgaard et al [ 27 ] found a significant effect of a stress-management intervention (CBT) on a lasting return to work among patients with work-related stress complaints. Dalgaard et al [ 28 ] found significant group effects of Work-focused cognitive behavioral intervention on perceived stress and memory when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Dalgaard et al [ 27 ] found a significant effect of a stress-management intervention (CBT) on a lasting return to work among patients with work-related stress complaints. Dalgaard et al [ 28 ] found significant group effects of Work-focused cognitive behavioral intervention on perceived stress and memory when compared to the control group. Eseadi et al [ 29 ] found a significant decline in depression was observed among the participants in the group after their exposure to rational emotive cognitive-behavioral coaching (RE-CBC).…”
Section: Introductionmentioning
confidence: 99%